Watermark face recognition authentication system - Mohd Rizal Mohd Isa (UPNM Press, 2022)
Watermarking techniques can be used effectively to protect the genuine ownership of biometric data, either to accept or reject. This book presents a proposal for a suitable and viable combination of a face recognition algorithm and a watermarking technique, namely a Principal Component Analysis (PCA) and Discrete Cosine Transform (DCT) combination that will ensure the authenticity of the data being transmitted in the face recognition system, which will then increase its level of security. The emphasis is on replay attack, which is recognizing and rejecting captured biometric data resubmitted into the system.